(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The article derives from the author’s experience with the short stories of Nelson Rodrigues originally known as Life as it is... The body of the article consists fundamentally in his discovery of the tales of the newspaper column "Life as it is" and the possibility of staging them. This resulted in a single theatre show, which was re-enacted several times. The conception however has always remained the same: the maintenance of the narrative text, playing with multiple ways of conveying the author’s voice through the actors. The article also describes and analyses the repertoire of resources of non-illusionist theatricality used in the scenic illustration of Nelson Rodrigues’ short stories.